2014
DOI: 10.1007/s10646-014-1339-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the sensitivity of seven marine and freshwater bioassays as regards antidepressant toxicity assessment

Abstract: The hazards linked to pharmaceutical residues like antidepressants are currently a major concern of ecotoxicology because they may have adverse effects on non-target aquatic organisms. Our study assesses the ecotoxicity of three antidepressants (fluoxetine, sertraline and clomipramine) using a battery of marine and freshwater species representing different trophic levels, and compares the bioassay sensitivity levels. We selected the following bioassays: the algal growth inhibition test (Skeletonema marinoi and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…Therefore, LMS may be exploited for rapid screening of pharmaceutical exposure. In addition, very recent studies have reported that tests on larval stages could represent a promising approach for marine species given their rapid responses, high sensitivity, and high ecological value . In our opinion, the concomitant analysis of multiple MOA relevant endpoints and biomarkers covers different routes of pharmaceutical interactions with marine organisms and may help in developing new biomonitoring strategies for the marine environment.…”
Section: Pharmaceutical Interactions With Marine Faunamentioning
confidence: 99%
“…Therefore, LMS may be exploited for rapid screening of pharmaceutical exposure. In addition, very recent studies have reported that tests on larval stages could represent a promising approach for marine species given their rapid responses, high sensitivity, and high ecological value . In our opinion, the concomitant analysis of multiple MOA relevant endpoints and biomarkers covers different routes of pharmaceutical interactions with marine organisms and may help in developing new biomonitoring strategies for the marine environment.…”
Section: Pharmaceutical Interactions With Marine Faunamentioning
confidence: 99%
“…Based on LC 50 and EC 50 values, the most sensitive tests were those performed on A. amphitrite naupliar larvae (Table 1). These values were much lower than those found for other marine and freshwater crustaceans commonly used as ecotoxicological models such as A. salina (4080 mg/L) or D. magna (1150 mg/L) (Minguez et al, 2014a(Minguez et al, , 2014b ( Table 2). Barnacles play important ecological roles in marine coastal environments, and the impairment of important behavior traits of barnacle larvae such as motility may have an indirect effect on the coastal systems as a whole (Wu et al, 1997).…”
Section: Discussionmentioning
confidence: 57%
“…2 and 4) (Christensen et al, 2007;Minagh et al, 2009). Another common model organism in ecotoxicological tests, the brine shrimp Artemia salina resulted to be very resistant to SRT, with a value of EC 50 of 4080 mg/L in 48 h-immobilization tests (Minguez et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations